Sztuka bez końca - Fer, Briony (Artium Quaestiones, 2019)
Translation into Polish of a text, orginally published in English, by the British scholar Briony Fer. It concerns the “studioworks” by the American artist Eva Hesse. The article discusses the difficulty of classifying and naming elements of Hesse’s objects which are produced or remain as an effect of her work in her studio. It also focuses on “minor”, lesser known and difficult to classify work by Hesse.